Effect of dynamic and static strength training using Thera-Band® on elite athletes muscular strength - Karakurt, S.; Aggon, E. (Archives of Budo, 2018)
Background and Study Aim: Many training scientists have concentrated on alternative models and materials to find the most efficient way to develop the strength for the last few decades. Thera-Band® is an alternative training tool used to enhance some motoric characteristics (flexibility and strength) by the athletes. The aim of the study is the knowledge about the effects of dynamic and static strength exercises when applied with Thera-Band® on the athlete`s strength indicators.